Pengaruh ISSI, JIBOR, Kurs JISDOR, dan JUB terhadap NAB Reksa Dana Syariah (Sucorinvest Sharia Equity Fund) - Andi Muhammad Nur; Muhammad Noval (Jurnal Pasar Modal dan Bisnis, 2022)
This study aims to determine the effect of the Indonesian Sharia Stock Index (ISSI), Jakarta Interbank Offered Rate (JIBOR), Jakarta Interbank Spot Dollar Rate (JISDOR), and Total Money Supply (JUB) on Net Asset Value of Sucorinvest Sharia Equity Fund. in the period January 2016-May 2021 in the short and long term. This study uses Autoregressive Distributed Lag (ARDL), in explaining the effect of ISSI, JIBOR, JISDOR, and JUB as independent variables on the NAV of Sharia Mutual Funds Sucorinvest Sharia Equity Fund as the dependent variable. In the short term, partially NAB at lag 1, ISSI at lag 0, 1 2, JIBOR at lag 1 and JISDOR at lag 0 have a significant effect on NAV. In the long term, only the ISSI variable has a significant effect on NAV while the JIBOR and JISDOR variables have no effect on NAV. The JUB variable has no effect on the NAV of Islamic mutual funds in the short and long term. The results of this study are expected to be additional literacy in the capital market and become a reference for investors in investing in mutual fund instruments.